Implementasi Edukasi Ekonomi Syariah Pada Siswa SMK IT Al-Izhar Pekanbaru - Zakir, Muhammad; Mairiza, Diany; Syaipudin, Muhammad; Hidayat, Hidayat; Reza, Saru; Hasda, Mifta (EL-EMIR INSTITUTE, 2025)
This community service is carried out for SMK IT Al Izhar Pekanbaru students, the purpose of this community service is to determine the level of understanding of SMK IT Al Izhar Pekanbaru students about the development of Islamic banks in Indonesia. The methods used in this community service activity are counseling, presentations and discussions. The results of the community service show that: The community service program for SMK IT Al Izhar Pekanbaru students can be organized well and run smoothly according to the activity plan that has been prepared, the results of this community service concluded that: First, SMK IT Al Izhar Pekanbaru students' understanding of the development of Islamic banks in Indonesia varies, some already understand, some are still hesitant, some even do not understand, Second, The achievement of the objectives of the community service program for SMK IT Al Izhar Pekanbaru students, the entire program that has been carried out with collaboration between business owners and community service workers has been carried out all and in accordance with the event rounddown and the time that has been determined previously.